Thunder Boy Jr. - Alexie, Sherman, 1966- (Little, Brown and Company, 2016)
"Thunder Boy Jr. wants a normal name ... one that's all his own. Dad is known as Big Thunder, but Little Thunder doesn't want to share a name"--